The Effects of Defects and Damage in the Mechanical Behavior of Ti6Al4V Lattices - Goodall, Russell; Hernandez-Nava, Everth; Jenkins, Sarah N. M.; Sinclair, Lorna; Tyrwhitt-Jones, Emily; Khodadadi, Mohammad A.; Ip, Donald H.; Ghadbeigi, Hassan (Frontiers in Materials, 2019)
With recent advances in manufacturing methods for metals with defined, complex shapes, the investigation of metallic lattice materials (metals containing significant porosity with a regular arrangement of the solid, frequently in the form of thin structural members or struts) has become more common. These materials show many interesting properties, and may have the capacity to be more highly engineered and optimized for a given application than the random structures of other microcellular metals, such as metallic foams and sponges, permit. However, the novel structure brings new structure-properties correlations to bear on the properties of the materials. This paper examines one type of these materials, titanium alloy lattices fabricated by Electron Beam Melting (EBM), a material which typically shows only limited plasticity on deformation. The overall mechanical response is governed by the cooperative deformation of a very large number of individual struts that make up the lattice, and thus there is great potential for significant impact from damage arising due to defects in individual struts in the assembly. We explore the effect of simulated processing defects (missing struts) on the lattice properties, and how deformation and failure is distributed across the lattice after the onset of failure. This understanding will be of great use in designing new metallic lattice structures with greater damage tolerance and resistance to failure.